Positive electrode for lithium ion secondary battery and lithium ion secondary battery

By controlling the dispersion of the conductive agent and active material in lithium-ion secondary battery positive electrodes through precise analysis and adjustment of the C/Fe value standard deviation, the method addresses the challenges of output characteristics and adhesion strength, resulting in improved battery performance.

JP2025056893APending Publication Date: 2025-04-09THE FURUKAWA BATTERY CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2023166410
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-09-27
Publication Date
2025-04-09

AI Technical Summary

Technical Problem

Existing methods for manufacturing lithium-ion secondary battery positive electrodes face challenges in achieving both good output characteristics and adhesion strength, as excessive shear force can collapse the secondary particle structure, while insufficient shear leads to poor dispersion and adhesion issues.

Method used

The solution involves using a cross-section polisher and scanning electron microscope to observe the positive electrode active material, conductive agent, and binder on the current collector, and performing element mapping analysis to achieve a standard deviation of the C/Fe value between 1.0 and 1.5, ensuring uniform dispersion and maintaining the secondary particle structure.

Benefits of technology

This approach allows for the achievement of both good output characteristics and adhesion strength of the electrodes, as the uniform dispersion of the conductive agent and active material maintains the secondary particle structure, enhancing the battery's performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025056893000001_ABST
    Figure 2025056893000001_ABST
Patent Text Reader

Abstract

To provide a positive electrode for a secondary battery and the secondary battery, capable of achieving both good output characteristics and electrode adhesion strength.SOLUTION: There is provided a positive electrode 4 for a lithium ion secondary battery according to the present invention, in which a current collector is coated with a positive electrode mixture paste containing lithium iron phosphate forming secondary particles as a positive electrode active material, a conductive agent, and a binder and rolled. When an SEM image of a cross section of a positive electrode mixture layer is divided into grids such that a region including 5 or more and 50 or less positive electrode active material secondary particles has 90 or more sections, each section having an actual size of 4 to 6 μm square, and elemental mapping analysis by energy dispersive X-ray spectrometry (EDS) is performed for each divided section, a standard deviation S of a C / Fe value (a ratio of the number of carbon atoms % to the number of iron atoms %) shown in the following expression (1) is 1.0≤S≤1.5, where C represents the number of carbon atoms %, Fe represents the number of iron atoms %, and i represents a section (i=1, 2, 3,..., N), and N represents the total number of sections.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a positive electrode for a lithium ion secondary battery and a lithium ion secondary battery. [Background technology]

[0002] A positive electrode for a lithium ion secondary battery is produced by applying a positive electrode mixture paste containing a positive electrode active material, a conductive agent, a binder, and a solvent to a metal foil current collector, and then drying the paste.

[0003] Lithium-containing composite oxides such as lithium cobalt oxide, lithium manganate, and lithium iron phosphate are used as positive electrode active materials, but since the active materials themselves do not have sufficient conductivity, conductive agents such as carbon black and graphite have been added to impart conductivity. The conductive agent has the role of forming conductive paths between active materials, and when fabricating electrodes, it is important to disperse the conductive agent uniformly to ensure as many conductive paths as possible.

[0004] Here, the lithium iron phosphate has an olivine crystal structure. The olivine structure is a very stable material and does not release oxygen from the active material even in abnormal cases such as overcharging, making it very safe. In recent years, lithium iron phosphate has been increasingly adopted for EVs (Electric Vehicles) and stationary lithium ion batteries due to its high safety. However, lithium iron phosphate has poorer electrical conductivity than other active materials due to the presence of P-O bonds (Reference: Sung-Yoon Chung and Yet-Ming Chiang 2003 Electrochem. Solid-State Lett. 6 A278). One method for imparting good electrical conductivity is to coat primary particles of lithium iron phosphate with carbon and turn them into secondary particles (see, for example, Patent Document 1). By adopting this method, the carbon-coated primary particles come into contact with each other, and the contact parts become conductive paths, improving electrical conductivity.

[0005] There is also a paste manufacturing method including a first step of dissolving a binder in a solvent, a second step of adding an active material and a conductive agent to the binder solution and kneading the mixture into a mass with a high solid content ratio, and a third step of diluting the mixture with a solvent to a viscosity value suitable for coating (see, for example, Patent Document 2). In this method, the amount of solvent is reduced in the second step, and the paste with a high solid content ratio is kneaded while applying a shear force, which is excellent in dispersing the conductive agent uniformly and can increase the conductivity of the electrode. However, in Patent Document 2, the shear force is too strong for the positive electrode active material that forms secondary particles, so that the secondary particle structure is destroyed and the conductive path is cut, which is likely to deteriorate the charge / discharge characteristics.

[0006] Furthermore, as a method for maintaining the secondary particle structure of the positive electrode active material, there is a paste manufacturing method including a step of dry-mixing the positive electrode active material with a conductive assistant and a binder to obtain a mixed powder, and a step of adding the entire amount of the solvent and kneading (see, for example, Patent Document 3). In this method, the entire amount of the solvent is added and kneaded in a state where no shear force is applied to the paste, so that the aggregate structure is maintained and good charge / discharge characteristics can be obtained. However, the method described in Patent Document 3 has a problem that the conductive assistant and binder are likely to form lumps due to poor dispersibility of the material. If the binder is unevenly distributed, the electrode strength decreases and adhesion failure is likely to occur. Poor adhesion of the electrode causes the material to slip off in the subsequent slitting process and rolling process. [Prior art documents] [Patent documents]

[0007] [Patent Document 1] Patent No. 7010402 [Patent Document 2] JP 2001-167756 A [Patent Document 3] Patent No. 5297110 Summary of the Invention [Problem to be solved by the invention]

[0008] As explained above, if the shear force applied to the positive electrode active material forming the secondary particles is too strong, the aggregate structure collapses and the output characteristics deteriorate, whereas if the shear force is too weak, the aggregate structure is maintained but the dispersibility of the material deteriorates, causing poor adhesion of the electrode.

[0009] The present invention has been made in view of the above, and has an object to provide a positive electrode for a lithium ion secondary battery and a lithium ion secondary battery that can achieve both good output characteristics and good adhesion strength of the electrode. [Means for solving the problem]

[0010] In order to solve the above problems, an embodiment of a positive electrode plate for a lithium ion secondary battery according to the present invention is a lithium ion secondary battery positive electrode in which a cross-section of a positive electrode mixture layer processed to be flat using a cross-section polisher (manufactured by JEOL Ltd.) is observed with a scanning electron microscope (SEM), a mixture containing a positive electrode active material, a conductive agent, and a binder is applied to a current collector and rolled, and the cross-section of the positive electrode mixture layer is observed with an SEM, an SEM image region containing 5 to 200 positive electrode active material secondary particles is divided into a lattice shape so that there are 90 or more sections each having an actual size of 4 to 6 μm square, and element mapping analysis is performed on each section using an energy dispersive X-ray spectrometer (EDS), and the standard deviation S of the C / Fe value (ratio of carbon atom number % to iron atom number %) represented by the following formula (1) satisfies 1.0≦S≦1.5.

number

[0011] By using the above method, the dispersibility of the conductive agent and the active material can be quantified. The C / Fe value indicates the carbon atom percentage relative to the iron atom percentage of one of the above-mentioned sections, and the standard deviation S indicates the standard deviation of the C / Fe value, that is, the dispersibility of the material. For example, a large standard deviation S means that carbon (conductive agent) and iron (active material) are unevenly distributed, and a small standard deviation S means that carbon and iron are uniformly distributed. When S<1.0, the secondary particle structure of the active material is maintained, so the output characteristics are good, but the material is unevenly distributed and poor adhesion occurs. When S>1.5, the material is uniformly distributed, but the secondary particle structure is collapsed, so the output characteristics deteriorate. The present invention is an electrode with 1.0≦S≦1.5, and since the material is dispersed while maintaining the secondary particle structure, it is possible to achieve both output characteristics and adhesion.

[0012] One way to control the standard deviation S, i.e. the dispersibility of the paste, is to adjust the solid content ratio of the paste when kneading. For example, if the solid content ratio is increased, the shear force applied to the paste during kneading will be stronger, and the conductive agent will be dispersed evenly. This will result in a smaller standard deviation S. Conversely, if the solid content ratio is decreased, the shear force will be weaker, making it harder for the conductive agent to disperse, and it will be unevenly distributed. This will result in a larger standard deviation S. The solid content ratio is the ratio of the active material, conductive agent, binder (and the solid mass of the dispersant if a dispersant is included) to the solvent mass. Therefore, the solid content ratio during kneading is adjusted by adjusting the ratio of the solid mass to the solvent mass. In the present invention, the solid content ratio is adjusted by adjusting the solvent mass. Effect of the Invention

[0013] According to the present invention, by appropriately dispersing a conductive agent while maintaining the aggregate structure of the positive electrode active material that forms secondary particles, it is possible to obtain a positive electrode for a lithium ion secondary battery and a lithium ion secondary battery that achieve both good output characteristics and electrode adhesion strength. [Brief description of the drawings]

[0014] [Figure 1]FIG. 1 is an exploded perspective view illustrating the configuration of a lithium ion secondary battery including a positive electrode for a lithium ion secondary battery according to one embodiment of the present invention. [Diagram 2] FIG. 2 is a flow chart showing a flow of producing a positive electrode composite paste for a lithium ion secondary battery positive electrode according to one embodiment of the present invention. [Diagram 3] FIG. 3 is a diagram in which a frame image equally divided into 90 sections is superimposed on a cross-sectional SEM image of the positive electrode mixture layer according to Example 1 of the present invention. [Figure 4] FIG. 4 is a diagram in which a frame image equally divided into 90 sections is superimposed on a cross-sectional SEM image of a positive electrode mixture layer according to Comparative Example 1 of the present invention. [Diagram 5] FIG. 5 is a diagram in which a frame image divided into 90 equal sections is superimposed on a cross-sectional SEM image of a positive electrode mixture layer according to Comparative Example 5 of the present invention. [Figure 6] FIG. 6 is a graph showing the standard deviation S of the C / Fe value in Examples 1 to 4 of the present invention and Comparative Examples 1 to 5. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0015] Hereinafter, the embodiment of the present invention will be described, but the present invention is not limited to the following description. In addition, various modifications and improvements can be made to the embodiment, and such modifications and improvements can also be included in the present invention. 1 shows a configuration example of a coin-type lithium ion secondary battery (coin cell) as an example of an embodiment, but the shape of the lithium ion secondary battery in the present invention is not particularly limited, and may be flat, cylindrical, rectangular, laminated, etc. Furthermore, the exterior body of the lithium ion secondary battery is not particularly limited, and known materials such as laminate film, aluminum, aluminum alloy, stainless steel, etc. can be used.

[0016] (Embodiment) FIG. 1 is an exploded perspective view illustrating the configuration of a lithium ion secondary battery including a positive electrode for a lithium ion secondary battery according to one embodiment of the present invention.

[0017] The lithium ion secondary battery 10 includes a case 1, a leaf spring 2, a spacer 3, a positive electrode 4, a separator 5, a negative electrode 6, a gasket 7, and a cap 8. The lithium ion secondary battery 10 is a coin-type lithium ion secondary battery including a lithium ion secondary battery positive electrode configured using a positive electrode current collector and a positive electrode mixture layer.

[0018] In the lithium ion secondary battery 10, the case 1 and the cap 8 are fixed by caulking or the like, and the inside is filled with a non-aqueous electrolyte. In the non-aqueous electrolyte secondary battery 10, the case 1, the gasket 7, and the cap 8 provide a liquid-tight seal. In addition, the spacer 3, the positive electrode 4, the separator 5, and the negative electrode 6 are biased toward the cap 8 by the leaf spring 2. This keeps each member in close contact with one another.

[0019] <Positive electrode> The positive electrode 4 is a positive electrode for a lithium secondary battery that includes at least a positive electrode current collector and a positive electrode mixture layer provided on one or both sides of the positive electrode current collector.

[0020] [Positive electrode current collector] Although there is no particular limitation on the material constituting the positive electrode current collector, it is preferable to use a metal, specifically, aluminum, nickel, stainless steel, titanium, and other alloys.

[0021] [Cathode active material] The positive electrode mixture layer is composed of a positive electrode active material, a conductive agent, and a binder. The positive electrode active material (also called electrode material) can be lithium iron phosphate, an olivine type compound that forms secondary particles. In this electrode material, it is preferable that 80% or more of the surface of the primary particles or the aggregates (secondary particles) formed by the aggregation of the primary particles is covered with a carbonaceous film containing carbon. The coverage of the carbonaceous film on the surface of the electrode material of this embodiment can be measured using a transmission electron microscope (TEM, Energy Dispersive Spectrometer: EDS) or the like.

[0022] When the average primary particle size of the positive electrode active material is 50 nm or less, the specific surface area becomes large and the ion diffusibility and electronic conductivity improve, but the amount of carbon that coats the carbonaceous material increases.When the average primary particle size is 400 nm or more, the amount of carbon that coats the carbonaceous material can be reduced, but the ion diffusibility and electronic conductivity decrease.

[0023] In addition, if the average secondary particle diameter of the positive electrode active material is less than 0.3 μm, it is difficult to obtain sufficient adhesion strength between the electrode current collector and the electrode material, and if a binder resin is included, the amount of binder resin is excessive, which may impair the battery capacity. On the other hand, if the average secondary particle diameter exceeds 50 μm, when an electrode for a lithium ion secondary battery is formed, a distribution of density of the electrode material is likely to occur in the electrode. As a result, the current density in the microscopic region of the electrode is different, and therefore the deterioration rate of the electrode material is different in the microscopic region of the electrode.

[0024] In consideration of these, in the present invention, the average primary particle size is set to be greater than 50 nm and less than 400 nm, and the average secondary particle size is set to be 5 μm or more and 30 μm or less.

[0025] [Conductive agent] The conductive agent is not particularly limited, and known or commercially available conductive agents can be used. For example, carbon black such as acetylene black and ketjen black, activated carbon, graphite, carbon fiber, carbon nanofiber, and carbon nanotubes can be used. The carbon nanotubes may be single-walled carbon nanotubes (SWCNT) or multi-walled carbon nanotubes (MWCNT) such as double-walled carbon nanotubes (DWCNT).

[0026] [Binding agent] The type of binder is not particularly limited, but examples of the binder that can be used include polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), polyvinylpyrrolidone (PVP), polyvinyl chloride (PVC), polyethylene (PE), polypropylene (PP), ethylene-propylene copolymer, styrene-butadiene rubber (SBR), and acrylic resin.

[0027] [Dispersant] A dispersant is not necessarily required, but may be added if it is desired to disperse the conductive agent more. A typical dispersant is, for example, polyvinylpyrrolidone (PVP).

[0028] [Electrode composition] In the electrode composition of the positive electrode 4, the higher the positive electrode active material ratio, the higher the energy density, the higher the conductive agent ratio, the better the electronic conductivity, and the higher the binder ratio, the higher the peel strength of the electrode coating surface. Considering these balances, the electrode composition is preferably such that the mass ratio of the positive electrode active material is 90.0 mass% or more and 95.0 mass% or less, the mass ratio of the conductive agent is 1.0 mass% or more and 5.0 mass% or less, and the mass ratio of the binder is 1.0 mass% or more and 5.0 mass% or less, relative to the total mass of the positive electrode plate composite layer. In this case, if the mass ratio of the positive electrode active material is less than 90.0 mass%, the energy density cannot be increased, whereas if the mass ratio of the positive electrode active material is more than 95.0 mass%, the energy density is increased, but the ratio of the conductive agent or binder to the positive electrode active material is decreased, thereby decreasing the electronic conductivity or peel strength. Furthermore, if the mass ratio of the conductive agent is less than 1.0 mass%, the electronic conductivity decreases, whereas if the mass ratio of the conductive agent is more than 5.0 mass%, the electronic conductivity improves, but the ratio of the binder to the conductive agent becomes insufficient, resulting in a decrease in peel strength. Furthermore, if the mass ratio of the binder is 1.0 mass % or less, the peel strength decreases, whereas if the mass ratio of the binder is more than 5.0 mass %, the binder becomes a resistive component, decreasing electronic conductivity.

[0029] [Coating process] The method of applying the positive electrode composite paste onto the current collector is not particularly limited, and a general coating method can be appropriately selected and used. A known coating method selected from gravure coating, gravure reverse coating, roll coating, Mayer bar coating, blade coating, knife coating, air knife coating, commart coating, slot die coating, slide die coating, dip coating, etc. can be used. In this embodiment, the current collector foil is coated and dried by table coating. At this time, for example, the temperature inside the furnace is set to 100°C, and the current collector foil is dried with hot air for 3 minutes. For example, an aluminum foil with a thickness of 20 μm is used as the current collector foil used for coating. Here, the coating amount on one side is 6 mg / cm. 2 Below this level, the output characteristics improve, but the capacity per unit area decreases. 2 In the above cases, the output characteristics decrease, but the capacity per unit area increases. Therefore, the coating amount is 6 mg / cm2 on one side. 2 Greater than 13mg / cm 2 In the present embodiment, for example, the coating amount on one side is 11 mg / cm 2 A single-sided coated electrode is produced so that The coating amount of the positive electrode was determined by cutting out a positive electrode to a certain area, peeling off the positive electrode composite layer from the current collector foil, measuring the mass, and dividing the obtained mass by the area. Similarly, the electrode density was determined by cutting out a positive electrode to a certain area, measuring the thickness of the positive electrode composite layer after removing the current collector foil, peeling off the positive electrode composite layer from the current collector foil, measuring the mass, and dividing the obtained mass by the volume obtained by multiplying the thickness and the area.

[0030] [Pressing process] The coated electrode was rolled using a press. The coating density of the electrode can be adjusted by adjusting the gap and press pressure of the press rolls of the press. If the electrode is rolled so that the coating density is 1.8 g / cc or less, the capacity per volume decreases. If the electrode is rolled so that the coating density is 2.2 g / cc or more, strong stress is applied to the current collector foil via the composite layer, causing electrode distortion and wrinkles. Taking these factors into consideration, the density set during rolling in the present invention is 2.0 g / cc. The press can be a mechanical press or a hydraulic press.

[0031] [solvent] The type of the solvent is not particularly limited, but solvents such as N-methyl-2-pyrrolidone, N,N-dimethylformamide, and N,N-dimethylacetamide can be used. When polyvinylidene fluoride is used as the binder, it is preferable to use N-methyl-2-pyrrolidone as the solvent.

[0032] <Negative electrode> The negative electrode 6 at least comprises a negative electrode current collector and a negative electrode mixture layer provided on one or both sides of the negative electrode current collector, and is capable of absorbing and releasing lithium ions.

[0033] <Nonaqueous electrolyte> The non-aqueous electrolyte contains a non-aqueous solvent in which a lithium salt is dissolved. The lithium salt may be, for example, one or a mixture of two or more selected from the group consisting of LiBF4, LiPF6, Li(FSO2)2N, and Li(CF3SO2)2N.

[0034] The non-aqueous solvent is not particularly limited, but may be, for example, one or a mixture of two or more selected from the group consisting of dimethyl carbonate (DEC), diethyl carbonate (DEC), dipropyl carbonate (DPC), ethyl methyl carbonate (EMC), ethylene carbonate (EC), propylene carbonate (PC), methyl propionate, methyl acetate, methyl formate, methyl butyrate, dioxolane, 2-methyltetrahydrofuran, tetrahydrofuran, dimethoxyethane, γ-butyrolactone, acetonitrile, and benzonitrile. In particular, DMC, DEC, DPC, EMC, EC, and PC are preferred. Among these, it is preferred to include EC, which is capable of forming a good coating on the negative electrode active material.

[0035] The non-aqueous electrolyte preferably further contains additives other than the lithium salts described above for the purpose of forming a good quality coating on the surface of the negative electrode active material by reductive decomposition during charging and discharging. The additives are not particularly limited, but examples thereof include vinylene carbonate, fluoroethylene carbonate, 1,3,2-dioxathiolane-2,2-dioxide (MMDS), 1,5,2,4-dioxadithiane-2,2,4,4-tetraoxide, tris(trimethylsilyl) phosphite, 1-propene-1,3-sultone, and Li2PO2F2. These additives may be used alone or in combination of two or more.

[0036] [Separator] The separator may be, for example, a porous sheet made of polymer or fiber, a nonwoven fabric separator, etc. The separator may also be one in which a ceramic layer, which is a heat-resistant insulating layer, is laminated on a porous substrate.

[0037] [SEM image] In this embodiment, the positive electrode 4 was processed using a cross-section polisher (manufactured by JEOL Ltd.) so that the cross section of the positive electrode composite layer was flattened, and the processed portion was photographed with a scanning electron microscope (SEM). The cross section of the positive electrode composite layer refers to a cut surface in the thickness direction of the layer.

[0038] In order to analyze the dispersion state of the active material and the conductive agent, it is necessary to include the active material and the conductive agent in the SEM image region. To this end, the SEM image region is set to a region containing 5 to 20 positive electrode active material secondary particles, so that the active material and the conductive agent can be reliably included in the image region. In addition, in order to accurately grasp the dispersion state of the active material and the conductive agent, it is preferable to divide the SEM image region into a grid shape so that there are 90 or more sections with an actual size of 4 to 6 μm square. In this case, if there are 90 or less sections, the sample size is small, so that the dispersion state may not be accurately analyzed. In addition, it is preferable to set the size of one section to 4 μm to 6 μm in order to accurately analyze the dispersion state. If one section is 4 μm square or less, the number of sections containing only the active material or only the conductive material increases significantly, and the number of sections containing both the conductive material and the active material decreases significantly, so that even if a clear difference is observed in the dispersion state of the electrode, there is a possibility that no difference will occur in the standard deviation S. Conversely, when the partitions are 6 μm square or larger, the number of partitions containing both conductive material and active material increases significantly, and the number of partitions containing only active material or only conductive material decreases significantly, so that even if a clear difference is observed in the dispersion state of the electrode, there may be no difference in the standard deviation S. By making the partitions 4 μm to 6 μm square, the ratio of partitions containing only active material or only conductive material and partitions containing both conductive material and active material is appropriate, so that the electrode dispersion state is reflected in the standard deviation S.

[0039] When the SEM image of the positive electrode 4 is divided and each section is subjected to element mapping analysis by an energy dispersive X-ray spectrometer (EDS), the standard deviation S of the C / Fe value (ratio of the number % of carbon atoms to the number % of iron atoms) shown in the following formula (1) satisfies 1.0≦S≦1.5.

number

[0040] In the present embodiment described above, a cathode mixture paste containing lithium iron phosphate forming secondary particles as a cathode active material, a conductive agent, and a binder is applied to a current collector and rolled to form a lithium ion secondary battery cathode, and a cross section of the cathode mixture layer is divided into 90 or more sections in a grid pattern, each section containing 5 to 50 secondary particles of the cathode active material, based on element mapping analysis by an energy dispersive X-ray spectrometer (EDS) for each section. The standard deviation S of the C / Fe value (ratio of carbon atom number % to iron atom number %) shown in the above formula (1) is 1.0≦S≦1.5. According to the present embodiment, by using a cathode 4 that satisfies the above conditions, it is possible to obtain a cathode for a lithium ion secondary battery and a lithium ion secondary battery in a good dispersion state while maintaining the aggregated structure of the cathode active material forming the secondary particles. EXAMPLES

[0041] The present invention will be specifically described below with reference to examples and comparative examples. Note that the present invention is not limited to the embodiments described in the examples.

[0042] Example 1 [Electrode materials and solvents] The electrode constituent materials used were a positive electrode active material (lithium iron phosphate), a conductive agent (carbon black (Li400) manufactured by Denka Co., Ltd.), and a binder (PVDF (KF polymer #9300) manufactured by Kureha Co., Ltd.). The ratio of materials was positive electrode active material / conductive agent / binder = 93 / 3 / 4, and in the present invention, 131.13 g of positive electrode active material, 4.23 g of conductive agent, and 5.64 g of binder were used. The solvent used in preparing the positive electrode composite paste was N-methyl-2-pyrrolidone (NMP: manufactured by Mitsubishi Chemical Corporation). The positive electrode composite paste was prepared according to the following steps (Mixing 1) to (Mixing 3) (see FIG. 2).

[0043] [Mixing] <Mixing 1> 4.23 g of carbon black as a conductive agent, 5.64 g of PVDF as a binder, and 141 g of NMP as a solvent were mixed at 2000 rpm for 2 minutes using a Thinky Mixer (manufactured by Thinky Corporation) to obtain a mixture. <Mixing 2> To the mixture prepared in the kneading 1, 131.13 g of lithium iron phosphate, which is a positive electrode active material, was added, and the mixture was mixed at 2000 rpm for 6 minutes using a Thinky Mixer (manufactured by Thinky Corporation) to obtain a mixture. <Mixing 3> A solvent was added so that the viscosity value, measured at 25°C and 60 rpm using a B-type viscometer (Toki Sangyo Co., Ltd.: BMII rotor No. 4), was 1000 mPa s or more and 7000 mPa s or less, and the mixture was kneaded using a Thinky Mixer (Thinky Corporation) to obtain a positive electrode composite paste.

[0044] [Electrode fabrication] The positive electrode mixture paste is applied to one side of the aluminum foil with a coating amount of 11 mg / cm 2 and dried with hot air at 100° C. for 10 minutes. Thereafter, the coating was rolled using a press machine to give a coating density of 2.0 g / cc, thereby preparing a positive electrode.

[0045] [Battery assembly] Charge / discharge evaluation and the like were performed using a 2032 type coin-type lithium secondary battery (hereinafter abbreviated as coin-type cell) having the structure described below.

[0046] A 300 μm thick lithium metal foil was attached to the surface of a 100 μm thick stainless steel plate negative electrode current collector to form a negative electrode layer, thereby preparing a negative electrode. A non-aqueous electrolyte solution was prepared by dissolving LiPF6 as a lithium salt at a ratio of 1.3 mol / L in a mixed solvent in which ethylene carbonate, ethyl methyl carbonate, and dimethyl carbonate were mixed in a volume ratio of 2:5:3. A coin-type cell was manufactured using the obtained positive electrode, negative electrode, electrolyte, and a separator made of a polyolefin microporous film in an argon atmosphere with a dew point of −50° C. or lower.

[0047] [Charge / discharge evaluation] The discharge load characteristics were evaluated using the coin cell prepared above. The discharge load characteristic test was performed by charging [0.2ItA-cc / cv-4.2V, 3h cut] and discharging [0.2 or 10.0ItA-cc, 2.0V cut].

[0048] [Peel test] The peel test was conducted in accordance with JIS standard JIS-K6854-1 (test method for peel adhesion strength, 90 degree peel), and the electrode strength was evaluated by measuring the peel strength at a sample width of 20 mm and a pulling speed of 50 mm / min.

[0049] [EDS analysis] The cross section of the positive electrode composite layer was observed by SEM, and the SEM image region containing 5 to 20 secondary particles of the positive electrode active material was divided into 90 equal sections, with each section being 6 μm square as the actual size, and element mapping was performed for each section by EDS. Fig. 3 is a diagram in which a frame image of the 90 equal sections is superimposed on the cross section SEM image of the positive electrode composite layer according to Example 1 of the present invention. The C / Fe value of each section was obtained from the obtained spectrum, and the standard deviation S was calculated from the above formula (1).

[0050] Whether the standard deviation S of the C / Fe value of the positive electrode plate falls within the range of 1.0≦S≦1.5 can be determined by the following procedure. First, the product cell was disassembled to remove the electrodes, which were then dried. Next, a cross-section polisher (manufactured by JEOL Ltd.) was used to process the cross section of the disassembled electrodes so that it was flat. After that, the processed parts were evaluated by SEM observation and EDS analysis.

[0051] Example 2 In Example 2, a coin-type cell was produced in the same manner as in Example 1, except that the amount of NMP added in the kneading 1 was 125 g.

[0052] Example 3 In Example 3, a coin-type cell was produced in the same manner as in Example 1, except that the amount of NMP added in the kneading 1 was 111 g.

[0053] Example 4 In Example 4, a coin-type cell was produced in the same manner as in Example 1, except that the amount of NMP added in the kneading 1 was 106 g.

[0054] Comparative Example 1 In Comparative Example 1, a coin-type cell was produced in the same manner as in Example 1, except that 159 g of NMP was added in kneading 1. Fig. 4 is a diagram in which a frame image in which each section is equally divided into 90 sections, each section being 6 µm square, is superimposed on a cross-sectional SEM image of the positive electrode mixture layer according to Comparative Example 1 of the present invention.

[0055] Comparative Example 2 In Comparative Example 2, a coin-type cell was produced in the same manner as in Example 1, except that 147 g of NMP was added in the kneading 1.

[0056] Comparative Example 3 In Comparative Example 3, a coin-type cell was produced in the same manner as in Example 1, except that the amount of NMP added in the kneading 1 was 98 g.

[0057] Comparative Example 4 In Comparative Example 4, a coin-type cell was produced in the same manner as in Example 1, except that the amount of NMP added in the kneading 1 was 86 g.

[0058] Comparative Example 5 In Comparative Example 5, a coin-type cell was produced in the same manner as in Example 1, except that 76 g of NMP was added in the kneading 1. Fig. 5 is a diagram in which a frame image in which each section is equally divided into 90 sections, each section being 6 µm square, is superimposed on a cross-sectional SEM image of the positive electrode mixture layer according to Comparative Example 5 of the present invention.

[0059] Table 1 shows the intermediate solid content values ​​at the second kneading stage and the intermediate solid content values ​​at the third kneading stage for Examples 1 to 4 and Comparative Examples 1 to 5. Table 2 also shows the standard deviation S of the C / Fe value, the peel strength of the electrode, and the charge / discharge characteristics in Examples 1 to 4 and Comparative Examples 1 to 5. [Table 1] [Table 2]

[0060] [About standard deviation S] From Table 2, the standard deviations S of Examples 1 to 4 satisfy 1.0≦S≦1.5. In contrast, the standard deviations S of Comparative Examples 1 and 2 were S>1.5. Moreover, the standard deviations S of Comparative Examples 3, 4, and 5 were S<1.0 (see Table 2 and FIG. 6). From the results shown in Tables 1 and 2, it can be seen that the lower the intermediate solid content ratio at the time of kneading 2 (Table 1), the larger the standard deviation S. This is because, as the intermediate solid content ratio at the time of kneading 2 becomes higher, the shear stress applied to the positive electrode composite paste during kneading of the positive electrode composite paste becomes larger, and the conductive agent is dispersed.

[0061] [About peel strength] Examples 1 to 4 and Comparative Examples 3 to 5, in which S≦1.5, have higher peel strengths than Comparative Examples 1 and 2, in which S>1.5 (see Table 2). This is presumably because the binder is dispersed without being unevenly distributed, resulting in higher peel strength. In Comparative Examples 1 and 2, in which S>1.5, the shear stress during kneading is small, and the binder is unevenly distributed without being dispersed, resulting in lower peel strength.

[0062] [Output characteristics] In Examples 1 to 4 and Comparative Examples 1 and 2, where S≧1.0, the 10 ItA discharge capacity / 0.2 ItA discharge capacity [%] was 70% or more (see Table 2). This is presumably because the secondary particle structure of the positive electrode active material was maintained and many conductive paths were formed, resulting in high output characteristics. On the other hand, in Comparative Examples 3 to 5, where S<1.0, the 10 ItA discharge capacity / 0.2 ItA discharge capacity [%] was less than 70% (see Table 2). This is presumably because the shear stress during kneading was large, causing the secondary particle structure to collapse and making it difficult to form conductive paths, resulting in a decrease in output characteristics.

[0063] [Conditions for achieving both output characteristics and peel strength] From the above results, in Examples 1 to 4, good output characteristics are maintained while the peel strength is maintained to a degree that does not cause the composite layer to slip off. From these results, in order to achieve both output characteristics and peel strength, if the standard deviation S calculated by the above formula (1) satisfies 1.0≦S≦1.5, a positive electrode plate in which the secondary particle structure of the positive electrode active material is maintained and the conductive agent and binder are appropriately dispersed can be obtained. [Explanation of symbols]

[0064] 1 case 2. Leaf spring 3 Spacer 4 Positive electrode 5. Separator 6 negative electrode 7 Gasket 8 Cap 10 Lithium-ion secondary battery

Claims

1. A lithium ion secondary battery positive electrode in which a positive electrode mixture paste containing lithium iron phosphate in which secondary particles are formed as a positive electrode active material, a conductive agent, and a binder is applied onto a current collector and rolled, wherein an SEM image of a cross section of the positive electrode mixture layer taken with a scanning electron microscope (SEM) is divided into a lattice shape such that an area containing 5 to 50 secondary particles of the positive electrode active material is divided into 90 or more sections each having an actual size of 4 to 6 μm square, and element mapping analysis is performed on each of the divided sections using an energy dispersive X-ray spectrometer (EDS), and the standard deviation S of the C / Fe value (ratio of carbon atom number % to iron atom number %) represented by the following formula (1) is 1.0≦S≦1.5: A positive electrode for a lithium ion secondary battery. [0010] Here, C is the number of carbon atoms (%), Fe is the number of iron atoms (%), i is a section (i=1, 2, 3, . . . , N), and N is the total number of sections.

2. With respect to the total mass of the positive electrode plate composite layer, the mass ratio of the positive electrode active material is 90.0 mass% or more and 95.0 mass% or less, the mass ratio of the conductive agent is 1.0 mass% or more and 5.0 mass% or less, and the mass ratio of the binder is 1.0 mass% or more and 5.0 mass% or less.

2. The positive electrode for a lithium ion secondary battery according to claim 1 .

3. The positive electrode for a lithium ion secondary battery according to claim 1 or 2, A negative electrode capable of absorbing and releasing lithium ions; A non-aqueous electrolyte; A lithium ion secondary battery comprising:

Citation Information

Patent Citations

  • Permanent magnet rotary machine

    JP1977097110A

  • Method of fabricating non-aqueous electrolyte secondary battery

    JP2001167756A

  • Positive electrode materials for lithium-ion secondary batteries, positive electrodes for lithium-ion secondary batteries, lithium-ion secondary batteries

    JP7010402B1